Numerical Analysis on MHD Stagnation-Point Flow Towards a Stretching Sheet using bvp4c Method with Slip Effect - Alisman, NorSyafikah; Md Shab, Noorzehan Fazahiyah (Enhanced Knowledge in Sciences and Technology, 2023)
The steady two-dimensional stagnation-point flow over a linearly stretching sheet in a viscous and incompressible fluid in the presence of a magnetic field is studied. This study is based on the research by Aman, Ishak, & Pop (2013). The derivation of the governing equation from nonlinear partial differential equation to nonlinear differential equation are done by using similarity transformation. The problem is solved numerically by using shooting technique through bvp4c method in MATLAB R2015a. The results obtained are analysed, compared and are depicted in tables and graphs. It is found that the present results are in good agreement with the previous results. As magnetic parameter M increases, the skin friction coefficient and the Nusselt number , decrease and increase respectively, while the heat transfer rate increases as the sheet stretches. Furthermore, both the skin friction coefficient and the heat transfer rate increases in the presence of slip.